Factors Associated with herb and dietary supplement use by young adults in the United States - Legedza Anna; Kemper Kathi J; Gardiner Paula; Phillips Russell S (BMC, 2007)
Abstract Background Little is known about the association between use of herbs and dietary supplements (HDS) and lifestyle/behavior factors in young adults in the US. Methods Analyzing the 2002 National Health Interview Survey (NHIS), we examined the patterns of HDS (excluding vitamins/minerals) use among young adults in the United States using descriptive statistics and logistic regression. Results In our sample of 18 to 30 year olds (n = 6666), 26% were current smokers, 24% were moderate/heavy drinkers, 43% had high physical activity, and 54% and 76% use prescription and over the counter (OTC) medications respectively. Non-vitamin, non-mineral HDS was used by 17% of the overall sample in the last 12 months. In the multivariable analysis, the lifestyle and behavioral factors associated with HDS use include: current smoking (odds ratio 1.41 95% CI [1.16-1.72]); being a former smoker (1.50 [1.15-1.95]); moderate/heavy alcohol use (2.02 [1.53-2.65]); high physical activity levels (2.45 [1.98-3.03]); and prescription medication use (1.51 [1.26-1.81]). Among HDS users, only 24% discussed their use with a health care professional. Conclusion Nearly one in five young adults report using non-vitamin/non-mineral HDS.